हिंदी

F(X) = 4x4 − 3x3 − 2x2 + X − 7, G(X) = X − 1 - Mathematics

Advertisements
Advertisements

प्रश्न

f(x) = 4x4 − 3x3 − 2x2 + x − 7, g(x) = x − 1

संक्षेप में उत्तर

उत्तर

Let us denote the given polynomials as

`f (x) = 4x^4 - 3x^3 - 2x^2 + x - 7`

`g(x) = x-1`

We have to find the remainder when f(x) is divided byg(x).

By the remainder theorem, when f(x) is divided by g(x) the remainder is

`f(1) = 4(1)^4 - 3(1)^3 - 2(1)^2 + 1-7`

        ` = 4 - 3- 2 + 1- 7`

         ` = -7`

Now we will show remainder by actual division

So the remainder by actual division is −7

shaalaa.com
  क्या इस प्रश्न या उत्तर में कोई त्रुटि है?
अध्याय 6: Factorisation of Polynomials - Exercise 6.3 [पृष्ठ १४]

APPEARS IN

आरडी शर्मा Mathematics [English] Class 9
अध्याय 6 Factorisation of Polynomials
Exercise 6.3 | Q 2 | पृष्ठ १४

वीडियो ट्यूटोरियलVIEW ALL [1]

Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×